IL-1b, IL-6 and IL-8 Levels in Gyneco-Obstetric Infections - Beatriz Basso; Francisco Giménez; Carlos López (Hindawi Limited, 2005)
Objective. During pregnancy cytokines and inflammatory mediators stimulate the expression of prostaglandin, the levels of which determine the onset of labor. The aim of this work was to study interleukin IL-1β, IL-6 and IL-8 levels in the vaginal discharge, serum and urine of pregnant women with genitourinary infection before and after specific treatment. One hundred and fifty-one patients were studied during the second or third trimester of their pregnancy.